Quantum material with quantum critical points and preparation method and application thereof
By optimizing the composition and preparation process of quantum materials composed of Ti, Fe, Cu and Sb elements, the precise regulation of quantum critical points is achieved, and the problems of poor controllability and consistency of existing quantum materials are solved, and materials with stable and unique quantum critical characteristics are obtained.
Patent Information
- Application Number
- CN202411646902.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-04-18
AI Technical Summary
The controllability and consistency of existing quantum materials are poor, making it difficult to achieve an effective connection between spin-related quantum states and quantum phase transitions, especially the conclusive evidence related to spin-glass states is elusive.
A quantum material composed of four elements: Ti, Fe, Cu and Sb, has the chemical formula TiFexCuySb, where 1
Accurate control of quantum critical points is achieved, materials with stable and unique quantum critical characteristics are obtained, controllability and consistency of material preparation are improved, and the demand for high-energy sub-materials by quantum technology is met.
Smart Images

Figure CN119843138A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of quantum materials, and in particular to a quantum material with a quantum critical point and a preparation method and application thereof. Background Art
[0002] Recent studies on quantum phase transitions (QPTs), especially those from long-range antiferromagnetic (AFM) or ferromagnetic (FM) order to paramagnetic heavy fermion liquids, have led to the development of the modern theory of quantum criticality. This emerging theoretical framework emphasizes that the behavior of local magnetic moments is as critical as the long-wavelength fluctuations of the order parameter in the classical Landau paradigm. A key consequence of this theory, known as the Kondo breakdown scenario, is that QPTs can arise from the transition of a spin glass to a heavy fermion liquid with an enlarged Fermi surface volume. A large number of theoretical studies have indicated that frustrated magnetoresistance systems with RKKY and Kondo interactions may undergo such QPTs by varying non-thermal control parameters such as magnetic field, pressure, or atomic substitution.
[0003] LiV2O4 was an early candidate for these interesting QPTs, exhibiting magnetic frustration due to the different valences of the two vanadium atoms. Although its specific heat can have a logarithmic temperature dependence, a hallmark of the onset of the quantum critical phase, and spin glass states have been observed upon Zn doping, subsequent studies have shown that the Kondo effect in LiV2O4 is negligible. Instead, its heavy fermion behavior arises primarily from strongly correlated a 1g Although other materials such as Pr2Ir2O7, Ge-substituted YbRh2Si2, and CePdAl have been investigated as potential candidates, firm experimental evidence linking spin-dependent quantum states to QPTs remains elusive, especially evidence related to spin glass states.
[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a quantum material with a quantum critical point and a preparation method and application thereof, aiming to solve the problem of poor controllability and consistency of existing quantum materials.
[0006] The technical solution of the present invention is as follows:
[0007] A quantum material with a quantum critical point, the quantum material is composed of four elements: Ti, Fe, Cu and Sb, and the chemical formula is TiFe x Cu y Sb, where 1<x+y<2.
[0008] The quantum material with a quantum critical point, wherein x=0.70, y=0.40.
[0009] The quantum material with a quantum critical point, wherein the magnetic field intensity of the quantum critical point of the quantum material can be controlled between 0.01-1T.
[0010] A method for preparing a quantum material having a quantum critical point comprises the steps of:
[0011] Weigh Ti, Fe, Cu and Sb raw materials and perform smelting treatment to obtain a molten mixture;
[0012] ball milling the molten mixture to obtain a mixed powder;
[0013] The mixed powder is subjected to spark plasma sintering treatment to obtain a quantum material with a quantum critical point.
[0014] The method for preparing a quantum material with a quantum critical point, wherein the purity of Ti is greater than or equal to 99.99%; the purity of Fe is greater than or equal to 99.99%; the purity of Cu is greater than or equal to 99.99%; and the purity of Sb is greater than or equal to 99.9%.
[0015] In the method for preparing a quantum material with a quantum critical point, Ti, Fe, Cu and Sb raw materials are stacked in order from bottom to top in order of high saturated vapor pressure to low saturated vapor pressure.
[0016] The method for preparing a quantum material with a quantum critical point, wherein the smelting current of the smelting treatment is 60mA-90mA, the single smelting time of the smelting treatment is 10s-30s, and the number of smelting times of the smelting treatment is 3-7 times.
[0017] The method for preparing a quantum material with a quantum critical point, wherein the rotation speed of the ball milling treatment is 1500r / min-1725r / min, and the time of the ball milling treatment is 0.2h-2h.
[0018] The method for preparing a quantum material with a quantum critical point, wherein the temperature of the spark plasma sintering treatment is 700°C-800°C, the time of the spark plasma sintering treatment is 5min-10min, and the pressure of the spark plasma sintering treatment is 30MPa-80MPa.
[0019] A quantum material with a quantum critical point and its application in quantum computing or quantum communication.
[0020] Beneficial effect: The present invention provides a quantum material with a quantum critical point and a preparation method and application thereof. The quantum material is composed of four elements: Ti, Fe, Cu and Sb, and has a chemical formula of TiFe x Cu y Sb, where 1<x+y<2. This quantum material has a transition structure from a spin glass state to a heavy fermion state, and possesses unique quantum critical properties. At 0K temperature and 0.13Tesla magnetic field, the material's resistance, specific heat, Greenansen constant, etc. show obvious quantum critical behavior. For example, the change in resistance with temperature conforms to linear behavior, and the change in specific heat with magnetic field conforms to a λ-type trend, with a maximum at 0.13Tesla. The magnetism shows obvious spin glass behavior below 1K. These characteristic indicators are significantly different from existing quantum materials, providing a new material basis for studying quantum critical phases and unconventional transport behaviors such as unconventional superconductivity. In addition, quantum materials with a quantum critical point for the transition from a spin glass state to a heavy fermion liquid state achieve precise control of the quantum critical point, obtaining materials with stable and unique quantum critical properties, while improving the controllability and consistency of material preparation to meet the research of quantum technology on high-performance quantum materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Non-stoichiometric TiFe 0.7 Cu 0.4 Schematic diagram of the crystal structure of Sb;
[0022] Figure 2 TiFe 0.7 Cu 0.4 iDPC image of Sb along the
[110] direction;
[0023] Figure 3 is the EDS spectrum of Fe atoms;
[0024] Figure 4 is the EDS spectrum of Cu atoms;
[0025] Figure 5 It is a process flow diagram of a method for preparing a quantum material having a quantum critical point according to the present invention;
[0026] Figure 6 The graph is a curve data showing the electrical and thermal properties of the quantum material prepared in Example 1 as a function of temperature and magnetic field;
[0027] Figure 7 The graph is a curve data showing the magnetic properties of the quantum material prepared in Example 2 as a function of temperature and magnetic field;
[0028] Figure 8 The quantum material TiFe prepared in Example 2 0.75Cu 0.5 Phase diagram corresponding to the quantum phase transition of Sb. DETAILED DESCRIPTION
[0029] The present invention provides a quantum material with a quantum critical point and a preparation method and application thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0030] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.
[0031] Magnetic frustration in antiferromagnetic insulators can induce quantum spin fluctuations that suppress long-range magnetic order (LRMO), leading to highly spin-correlated ground states found in exotic materials such as quantum spin liquids and spin glasses. Magnetic frustration can also occur in heavy fermion metals, where it interacts with the RKKY magnetic interaction between localized magnetic moments and their magnetic screening by conduction electrons, a phenomenon known as the Kondo effect. When the interplay between these competing forces and the associated quantum fluctuations becomes significant, it can lead to new quantum critical phases and behaviors. By exploring different types of quantum phase transitions (QPTs) and their evolution, one can gain unprecedented insight into the origin of quantum criticality in exotic metals, which is one of the most pressing problems in many-body physics.
[0032] However, conclusive experimental evidence linking spin-dependent quantum states to QPTs in existing candidate quantum materials remains elusive, especially evidence related to spin glass states.
[0033] Based on this, the present invention provides a quantum material with a quantum critical point, wherein the quantum material is composed of four elements: Ti, Fe, Cu and Sb, and has a chemical formula of TiFe x Cu y Sb, where 1<x+y<2.
[0034] In this embodiment, the quantum material has a transition structure from a spin glass state to a heavy fermion state, and has unique quantum critical properties. At 0K temperature and 0.13Tesla magnetic field, the material's resistance, specific heat, Greenansen constant, etc. show obvious quantum critical behavior, for example, the change of resistance with temperature conforms to linear behavior, the change of specific heat with magnetic field conforms to the λ-type trend, and a maximum value appears at 0.13Tesla, and the magnetism shows obvious spin glass behavior below 1K temperature. These characteristic indicators are significantly different from existing quantum materials, and provide a new material basis for studying quantum critical phases and unconventional transport behaviors such as unconventional superconductivity. In addition, quantum materials with a quantum critical point that transitions from a spin glass state to a heavy fermion liquid state realize precise control of the quantum critical point, obtain materials with stable and unique quantum critical properties, and at the same time improve the controllability and consistency of material preparation to meet the research of quantum technology on high-performance quantum materials.
[0035] Specifically, the quantum material TiFe x Cu y The chemical composition of Sb has been theoretically calculated and experimentally verified to be able to induce the material to form a special crystal structure and electronic state, which has a key influence on the generation and characteristics of the quantum critical point. The present invention can accurately control the position and characteristics of the quantum critical point by optimizing the material composition and preparation process. The quantum critical point can be set within a specific temperature and magnetic field range according to actual needs. For example, the magnetic field intensity of the quantum critical point can be controlled between 0.01T-1T. This precise control capability makes it possible to develop devices with specific quantum characteristics.
[0036] In some embodiments, x is between 0.7-0.75 and y is between 0.4-0.5.
[0037] In some embodiments, x=0.70, y=0.40. Taking x=0.70, y=0.40 as an example, TiFe 0.7 Cu 0.4 The magnetic frustration in Sb originates from the intrinsic disorder within the Fe and Cu sites, and a magnetic field-induced quantum critical point (QCP) is observed through detailed ultralow temperature thermodynamic measurements, including specific heats and Greenansen constants; when crossing this QCP, Hall measurements show an increase in the Fermi surface volume, consistent with the Kondo breakdown scenario, which is also partially supported by resistivity measurements, which indicate enhanced screening of localized magnetic moments. In addition, direct current (dc) and alternating current (ac) magnetic susceptibility measurements identify a cluster spin glass ground state, in which the magnetic entities are spin clusters rather than isolated atomic spins, and are gradually suppressed with increasing magnetic field.
[0038] Specifically, the non-stoichiometric TiFe 0.7 Cu 0.4The crystal structure diagram of Sb is shown in Figure 1 As shown, it can be seen that Ti and Sb atoms form two interpenetrating face-centered cubic lattices, while Fe and Cu atoms partially and randomly occupy the 4c (red) and 4d (blue) sites within the structure; Figure 2 is the iDPC image along the
[110] direction, Figure 2 The inset is the energy dispersive spectroscopy (EDS) spectrum of Ti and Sb atoms, showing their periodic distribution and regular structural order. Figure 3 is the EDS spectrum of Fe atoms, Figure 4 are the EDS spectra of Cu atoms, both highlighting their random distribution and indicating chemical disorder as they occupy the 4c and 4d sites.
[0039] In some embodiments, the magnetic field strength at the quantum critical point of the quantum material can be regulated between 0.01-1 T. At 0 K and 0.13 T, the resistance, specific heat, etc. of the quantum material show obvious quantum critical behavior, the resistance changes with temperature in a linear manner, and the specific heat changes with the magnetic field showing a λ variation trend; the magnetic field strength at the quantum critical point can be regulated between 0.01-1 T.
[0040] In addition, Figure 5 As shown, the present invention also provides a method for preparing a quantum material having a quantum critical point, comprising the steps of:
[0041] Step S10: weighing Ti, Fe, Cu and Sb raw materials and performing smelting treatment to obtain a molten mixture;
[0042] Step S20: ball milling the molten mixture to obtain a mixed powder;
[0043] Step S30: performing spark plasma sintering on the mixed powder to obtain a quantum material with a quantum critical point.
[0044] In this embodiment, a simple and easy preparation method is adopted, and technologies such as metal smelting, mechanical alloying and spark plasma sintering are used to easily realize large-scale production; this not only reduces production costs, but also improves production efficiency, which is conducive to the wide application of quantum materials in practice. In addition, the samples obtained by the above preparation method adopted by the invention are more uniform, which is very important for quantum materials to show obvious quantum phase transition behavior.
[0045] Specifically, the quantum material prepared by this method has a transition structure from the spin glass state to the heavy fermion state, and has unique quantum critical properties. At 0K temperature and 0.13Tesla magnetic field, the material's resistance, specific heat, Greenansen constant, etc. show obvious quantum critical behavior. For example, the change of resistance with temperature conforms to linear behavior, and the change of specific heat with magnetic field conforms to the λ-type trend, with a maximum at 0.13Tesla. The magnetism shows obvious spin glass behavior below 1K. These characteristic indicators are significantly different from those of existing quantum materials, providing a new material basis for studying quantum critical phases and unconventional transport behaviors such as unconventional superconductivity.
[0046] In some embodiments, the purity of Ti is greater than or equal to 99.99%; the purity of Fe is greater than or equal to 99.99%; the purity of Cu is greater than or equal to 99.99%; the purity of Sb is greater than or equal to 99.9%. Using high-purity Ti, Fe, Cu and Sb as raw materials for preparing quantum materials can improve the purity of quantum materials without being affected by impurities on the quantum critical point.
[0047] In some embodiments, Ti, Fe, Cu and Sb raw materials are stacked in order from bottom to top according to the saturated vapor pressure of the material, so as to prevent the metal raw materials with high saturated vapor pressure from volatilizing due to heat and affecting the stoichiometric ratio of the quantum material.
[0048] Specifically, elements with high saturated vapor pressure, such as Sb, are placed at the bottom, and the order of the other three is not required. This can ensure that the metal will not volatilize due to heat, and a highly accurate stoichiometric ratio quantum material can be obtained.
[0049] In some embodiments, the smelting current of the smelting process is 60mA-90mA, the single smelting time of the smelting process is 10s-30s, and the number of smelting times of the smelting process is 3 times-7 times. Controlling the key parameters during the smelting process can ensure that different types of metals can be completely melted and finally fused together.
[0050] Specifically, in step S10, the raw materials are placed in a metal smelting furnace, wherein elements with high saturated vapor pressure such as Sb are placed at the bottom, and are repeatedly smelted 3-7 times under argon protection until they are in a round cake shape. During the smelting process, the smelting current is controlled between 60mA and 90mA, and the single smelting time is 10s to 30s, so as to ensure that different types of metals can be completely melted and melted together to form a molten mixture.
[0051] In some embodiments, the ball milling speed is 1500 r / min-1725 r / min, and the ball milling time is 0.2 h-2 h. By controlling the parameters of the ball milling within the above range, the particle size of the mixed powder after ball milling can be adjusted to reach the nanometer level.
[0052] In some embodiments, 1-3 large stainless steel balls and 2-6 small stainless steel balls are further used in the ball milling process, and the small balls are used to fill the gaps between the large balls to improve the particle size uniformity of the mixed powder after the ball milling process.
[0053] It should be noted that large stainless steel balls and small stainless steel balls are relative, and their size ratio and number can be configured according to the amount of raw materials.
[0054] In some embodiments, the spark plasma sintering process is performed at a temperature of 700°C to 800°C, a time of 5 min to 10 min, and a pressure of 30 MPa to 80 MPa. During the sintering process, precise control of parameters such as pressure, temperature, heating rate, and time is crucial to forming an ideal crystal structure and microstructure, which directly affects the quantum properties of the material and the location and properties of the quantum critical point.
[0055] In some embodiments, the heating rate of the spark plasma sintering process is controlled at 80° C. / min-120° C. / min to ensure that the material is heated evenly.
[0056] In addition, the present invention also provides an application of a quantum material with a quantum critical point in quantum computing or quantum communication.
[0057] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.
[0058] Example 1
[0059] By TiFe 0.7 Cu 0.4 Sb component Weigh Ti, Fe, Cu and Sb raw materials, put the raw materials into a metal melting furnace, among which elements with high saturated vapor pressure such as Sb are placed at the bottom, and repeatedly melt them 5 times under argon protection until they are in a round cake shape, and control the key parameters in the melting process, such as melting current 80mA, single melting time 15S;
[0060] The smelted sample is placed in a stainless steel ball mill, stainless steel balls are added, and the ball mill is performed for 0.2 hours under argon protection. For example, the argon pressure is kept stable, the ratio of the stainless steel balls is two large stainless steel balls and four small stainless steel balls, and the rotation speed is 1725r / min.
[0061] The mixed powder was loaded into a graphite mold and sintered at 750°C for 5 minutes under a pressure of 50 MPa using spark plasma sintering technology. During the sintering process, the heating rate was controlled at 100°C / min to ensure that the material was heated evenly, thus obtaining a quantum material with a quantum critical point.
[0062] The performance test results of the material prepared in this example show that under a magnetic field of 0.13 Tesla, the electrical and thermal properties of the material exhibit expected quantum critical behavior, such as Figure 6 As shown, Figure 6 A is the electron specific heat coefficient under different magnetic fields, B is the electron specific heat coefficient measured at 64mK, which shows an obvious peak near 0.13Tesla, C is the temperature scale under different magnetic fields, D is the magnetocaloric effect measured under different magnetic fields, E is the magnetic Greenansen parameter, the solid line is the best fit of the data, F is the resistivity under different magnetic fields, G is the magnetic field dependence of the Hall resistivity at different temperatures, and H is the effective Hall coefficient at different temperatures. For example, by Figure 6 The specific heat data shown in A and B in the figure can be obtained Figure 6 From the phase diagram shown in C, it can be determined that a quantum phase transition occurs near 0.13T, and then Figure 6 The temperature-dependent electrical transport behavior of D, E, F, G, and H in the graph further confirms the existence of this quantum phase transition.
[0063] Example 2
[0064] By TiFe 0.75 Cu 0.5 Sb component Weigh Ti, Fe, Cu and Sb raw materials, put the raw materials into a metal melting furnace, among which elements with high saturated vapor pressure such as Sb are placed at the bottom, and repeatedly melt them 5 times under argon protection until they are in a round cake shape, and control the key parameters in the melting process, such as melting current 70mA, single melting time 30S;
[0065] The sample obtained after smelting was placed in a stainless steel ball milling jar, stainless steel balls were added, and ball milling was performed for 1 hour under the protection of argon atmosphere. During this process, parameters such as the number of stainless steel balls and the rotation speed can be adjusted according to the amount of raw materials and the amount of doping.
[0066] The mixed powder was loaded into a graphite mold and sintered at 700°C for 10 minutes under a pressure of 60 MPa using spark plasma sintering technology. During the sintering process, the heating rate was controlled at 80°C / min to ensure the quality of the material and obtain a quantum material with a quantum critical point.
[0067] The performance test results show that the material also has good quantum properties and expected quantum critical behavior under the corresponding conditions. Specifically, at 0.2 Tesla, the material's magnetism shows a change relationship that is consistent with the theory, such as Figure 7 As shown, Figure 7 A is the DC magnetic susceptibility measured in the range of 1.8K to 0.4K, B is the zero-field magnetic specific heat coefficient and the corresponding magnetic entropy, C is the real part of the AC magnetic susceptibility measured under zero magnetic field, D is the linear fit of the freezing temperature represented by the red data, E is the frequency dependence of the spin glass freezing temperature, and F is the magnetic field dependence of the magnetic susceptibility. As the magnetic field increases, the peak value is gradually suppressed, indicating that the cluster spin glass state is weakened. From Figure 7 It can be seen from A and B in the figure that the sample presents a spin glass state at low temperature and low magnetic field. As the magnetic field increases, the spin glass freezing peak is gradually suppressed. Figure 7 As shown in F, it corresponds to the quantum phase transition from the spin glass state to the heavy Fermi liquid state. This transition point corresponds to the quantum phase transition point, as shown in Figure 8 shown.
[0068] In summary, the present invention provides a quantum material with a quantum critical point and a preparation method and application thereof. The quantum material is composed of four elements: Ti, Fe, Cu and Sb, and has a chemical formula of TiFe x Cu y Sb, where 1<x+y<2. This quantum material has a transition structure from a spin glass state to a heavy fermion state, and possesses unique quantum critical properties. At 0K temperature and 0.13Tesla magnetic field, the material's resistance, specific heat, Greenansen constant, etc. show obvious quantum critical behavior. For example, the change in resistance with temperature conforms to linear behavior, and the change in specific heat with magnetic field conforms to a λ-type trend, with a maximum at 0.13Tesla. The magnetism shows obvious spin glass behavior below 1K. These characteristic indicators are significantly different from existing quantum materials, providing a new material basis for studying quantum critical phases and unconventional transport behaviors such as unconventional superconductivity. In addition, quantum materials with a quantum critical point for the transition from a spin glass state to a heavy fermion liquid state achieve precise control of the quantum critical point, obtaining materials with stable and unique quantum critical properties, while improving the controllability and consistency of material preparation to meet the research of quantum technology on high-performance quantum materials.
[0069] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A quantum material having a quantum critical point, characterized in that: The quantum material is composed of four elements: Ti, Fe, Cu and Sb, and its chemical formula is TiFe x Cu y Sb, where 1<x+y<2.
2. The quantum material having a quantum critical point according to claim 1, characterized in that: x=0.70, y=0.
40.
3. The quantum material having a quantum critical point according to claim 1, characterized in that: The magnetic field intensity of the quantum critical point of the quantum material can be adjusted between 0.01-1T.
4. A method for preparing a quantum material having a quantum critical point as claimed in any one of claims 1 to 3, characterized in that: Includes steps: Weigh Ti, Fe, Cu and Sb raw materials and perform smelting treatment to obtain a molten mixture; ball milling the molten mixture to obtain a mixed powder; The mixed powder is subjected to spark plasma sintering treatment to obtain a quantum material with a quantum critical point.
5. The method for preparing a quantum material having a quantum critical point according to claim 4, characterized in that: The purity of Ti is greater than or equal to 99.99%; the purity of Fe is greater than or equal to 99.99%; the purity of Cu is greater than or equal to 99.99%; The purity of Sb is greater than or equal to 99.9%.
6. The method for preparing a quantum material having a quantum critical point according to claim 4, characterized in that: The Ti, Fe, Cu and Sb raw materials are stacked in order from bottom to top according to the saturated vapor pressure of the material.
7. The method for preparing a quantum material having a quantum critical point according to claim 4, characterized in that: The smelting current of the smelting process is 60mA-90mA, the single smelting time of the smelting process is 10s-30s, and the number of smelting times of the smelting process is 3 times-7 times.
8. The method for preparing a quantum material having a quantum critical point according to claim 4, characterized in that: The rotation speed of the ball milling treatment is 1500r / min-1725r / min, and the time of the ball milling treatment is 0.2h-2h.
9. The method for preparing a quantum material having a quantum critical point according to claim 4, characterized in that: The temperature of the spark plasma sintering treatment is 700° C.-800° C., the time of the spark plasma sintering treatment is 5 min-10 min, and the pressure of the spark plasma sintering treatment is 30 MPa-80 MPa.
10. Use of the quantum material having quantum critical points as claimed in any one of claims 1 to 3 in quantum computing or quantum communication.